Postharvest physicochemical and nutritional properties of Tomato fruit at different maturity stages affected by physical impact - Md. Safiuddin Bapary; Md. Nahidul Islam; Nikhil Kumer; Mahmudul Hasan Tahery; Mohammad Abdulla Al Noman; Mohammed Mohi-Ud-Din (Applied Food Research)
Tomatoes are a globally significant vegetable valued for their nutritional benefits and culinary versatility. However, they are prone to mechanical damage, such as dropping and bruising, during harvesting and handling, which can impair their physicochemical and nutritional properties, reduce shelf life and marketability. This study aimed to evaluate the effects of dropping and bruising on the physicochemical and nutritional properties of tomatoes. Vanessa F1 Hybrid tomatoes at two maturity stages, Breaker (II) and Red ripe (VI) were dropped from a height of 90 cm and stored at various temperatures for 15 days. We assessed changes in firmness, total soluble solids (TSS), titratable acidity, respiration rate, vitamin C, and mineral contents (K and Ca) over the storage period. Dropped tomatoes exhibited significantly increased internal bruising and accelerated deterioration over time, with Red ripe tomatoes being more affected. Firmness, TSS, titratable acidity, and vitamin C content significantly decreased, while respiration rates and mineral content also reduced due to dropping. Breaker stage tomatoes showed better retention of firmness and nutrient content compared to Red ripe stage tomatoes, particularly when stored at 5 °C. Mechanical damage from dropping significantly degrades the quality of tomatoes, affecting their physical and chemical properties. The study highlights the importance of minimizing mechanical injuries to maintain tomato quality and extend shelf life. This knowledge can aid in developing improved postharvest handling practices to enhance the competitiveness and sustainability of the tomato industry.